Tactical Aircraft Modernization : Issues for Congress. (U.S. Congressional Research., 2005)
Provides background on and analysis of DOD program to modernize tactical aircraft in U.S. military; addresses issues of affordability, aircraft capability, force structure, service roles and missions, industrial base, and modernization vs. transformation; and surveys Congressional action.